Broyden's Method for Solving Variational Inequalities with Global and Superlinear Convergence (Journal of Computational Mathematics, 2000)
In this paper, we establish a quasi-Newton method for solving the KKT system arising from variational inequalities. The subproblems of the proposed method are lower-dimensional mixed linear complementarity problems. A suitable line search is introduced. We show that under suitable conditions, the proposed method converges globally and superlinearly.